Transformative Islamic Education Management in The Revitalization of The Mapalus North Minahasa Muslim Community - Rivai Bolotio; Nasruddin Yusuf (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study analyzes the revitalization of the Mapalus tradition through Islamic education within the Muslim community of North Minahasa. It constructs a concept of transformative Islamic education management in this revitalization process. The research hypothesis suggests that transformative Islamic education management revitalizes the Mapalus tradition through Islamic education, fostering social change within the Muslim community and the broader North Minahasa society. This study employs a qualitative approach, integrating transformative Islamic education and educational management perspectives. Data was collected through interviews, observations, and literature studies in Kema, Kauditan, Wori, West Likupang, and East Likupang. The findings reveal that the revitalization of Mapalus through Islamic education is integrated into school curricula and social programs aligned with village programs within the Muslim community of North Minahasa. The transformative Islamic education management concept identified in this study includes personnel management, curriculum management, student affairs management, and public relations management, which serve as novel contributions to this research.